Sequence and Structure of the Mouse Connexin45 Gene. Issue 5 (October 2001) - Baldridge, Dustin; Lecanda, Fernando; Shin, Chan-Soo; Stains, Joseph; Civitelli, Roberto
Abstract : The connexin45 (Cx45) gene was cloned from a mouse genomic Bacterial Artificial Chromosome library. Approximately 8.4 kb of the genomic DNA was sequenced, and the structure of the Cx45 gene was determined. The mouse Cx45 gene is composed of 3 exons, with the entire coding sequence contained within exon III (EMBL Accession Number AJ300716). This structure is unique for the Cx45 gene, since all other members of the connexin family have only two exons. In addition, computer analysis reveals a potential TATA box and two putative AP-1 binding sites in the 5′ region of the gene. Sequence alignment with connexin43 indicates substantial homology in the intronic sequences upstream of the 3′ exons of the two genes, suggesting that the Cx45 gene is inherently similar to the rest of the connexin family, and that it probably evolved from an ancestor common to the other connexins.